Geochemical-based appraisal of karst groundwater quality, west Nile Valley, central Egypt, for drinking and irrigation - Hassan Alzahrani; Abdullah Basaloom; Sayed Mosaad (Journal of Hydrology: Regional Studies)
Study region: west El-Minya region is located West Nile Valley in the central part of Egypt.Study focus: The research aims to evaluate the geochemical processes affecting the groundwater and its suitability for drinking and agricultural purposes. This was achieved through integrated the analysis of ionic concentration data, using Piper and Gibbs diagrams, ionic ratios, multivariate analysis, and Water Quality Indices (WQI).New hydrological insight: Funding indicated that the groundwater varies from fresh to brackish. The water types are characterized by Na-Cl-SO4 and Ca-Mg-SO4-Cl. Binary diagrams and factor analysis identified key mechanisms regulating major ion chemistry, including silicate weathering and ion exchange, with a minor contribution from carbonate and gypsum dissolution. The Drinking Water Quality index (DWQI) indicated that 75 % of groundwater samples are appropriate for drinking, especially in the southern and middle of the study area. Various agricultural indices were used to assess groundwater suitability for irrigation, indicating that most samples are suitable for irrigation use. The Irrigation Water Quality Index (IWQI) indicated that 42.86 % of the groundwater samples fell in a moderate restriction, while the rest of the sample was divided between the high and low restriction classes. The study shows vulnerability in water quality, highlighting the need for improved groundwater management. Adjusting watering frequency and using modern irrigation methods, like drip and sprinkler systems, can enhance water-use efficiency and reduce aquifer depletion.